Analysis of Added Value Brownies Product Using the Hayami Method (Case Study: Syiaghi MSME in Pekanbaru City) - Arum Rovarti Ningsih; Pramana, Angga; Putri, Nadya Novianti Dwi; Ihsan, Fikratul; Endyra, Fadlila; Masyitah, Masyitah (Journal of Engineering Science and Technology Management, 2026)
Syiaghi MSMEs have turned their brownie business into a value-added and competitive venture. A study to analyze the added value and competitiveness of brownies produced by Syiaghi MSMEs in PekanbaruThis study applies a quantitative approach using both primary and secondary data. Primary data was collected through direct observation (survey) at Syiaghi MSMEs and interviews with business owners. Secondary data was collected through library studies and other documents. Respondents in this study were determined using the purposive sampling method. Respondents were selected based on the type of brownies marketed (baked brownies), high daily production volume, and marketing to several campuses and stores. The selected respondents were business actors from Syiaghi MSMEs in Pekanbaru City. The analysis of the added value of brownies used the Hayami method. Based on the results of the research conducted on Syiaghi MSMEs with brownie products, it can be concluded that processing flour into brownies provides positive added value. The added value obtained was IDR 398,792 with an added value ratio of 71%, which is relatively high. This indicates that the processing is able to significantly increase the economic value of the product compared to the raw materials. Syiaghi SME is able to manage the production process efficiently through a combination of raw materials, labor, technology, and appropriate packaging. The high added value contributes positively to business profits, production efficiency, and the competitiveness of brownies in the market, making this business viable and promising for further development.